Drosophila NK-homeobox genes. - Kim, Y (1989)
Four Drosophila melanogaster homeobox genes were found by screening a genomic DNA library with oligodeoxynucleotides that correspond to a conserved amino acid sequence that is part of the putative of homeobox proteins that recognizes nucleotide sequences in DNA. The amino acid sequences of NK-2, NK-3, and NK-4 homeoboxes are more closely related to one another (59-66% homology) than they are to other Drosophila homeoboxes (28-54% homology), whereas the homeobox of NK-1 is most closely related, in order of decreasing homology, to muscle segment homeobox, zerknüllt-1, NK-3, and distal-less homeoboxes. Three of the genes, NK-1, NK-3, and NK-4, comprise a cluster of homeobox genes located in the 93E1-5 region of the right arm of the third chromosome, whereas the fourth homeobox gene, NK-2, is located in the 1C1-5 region of the X chromosome.